Development of thumbprint recognition system using Matlab / Wan Hasnizam Wan Hassan - Wan Hassan, Wan Hasnizam
Biometric is a technology, which identifies a person based on his physiology or behavioral characteristics. Thumbprint identification and recognition is one of the biometrics method available that has been widely used in various applications because of it is reliability and accuracy in the process of recognizing and verifying a person identity. The project highlights a thumbprint recognition system by using MATLAB software with the aid of Neural Network. A created program converts the thumbprint images to histogram data, and it can be used as input to neural network and trained. The algorithm used in order to achieve the result is called feedforward backpropagation neural network.